ANALISIS KESULITAN BELAJAR SISWA PADA MATERI SISTEM PENCERNAAN PADA MANUSIA DI KELAS VIII MTs NEGERI 1 PONTIANAK - Sari, Tika; Afandi, Afandi; Tenriawaru, Andi Besse (Universitas Tanjungpura, 2023)
The study serves to analyze the percentage of learning difficulties, the level of study difficulties, and the factors that lead to class VIII C MTsN 1 Pontianak in human digestive material. This kind of research is quantitative with the shape of case studies. This study sample was a student VIII C of the year 2020/2021. The research instruments used are diagnostic tests that function to identify students who have learning difficulties, questionnaires, and interviews to discern the underlying factors behind learning difficulties. Studies show a percentage of students learning difficulties in human digestive material 61.87% with difficulties category. The level of learning difficulties consists (level I) of 26,67% small learning difficulties (level II) of 33.33%, and heavy difficulties (level III) of 40,00%. The causes of student learning difficulties caused internal factors (43.78%) with sufficient category, and learning difficulties caused external factors (53.67%) with sufficient category